Lactobacillus rhamnosus protects human colonic muscle from pathogen lipopolysaccharide‐induced damage. Issue 12 (1st October 2013) - Ammoscato, F.; Scirocco, A.; Altomare, A.; Matarrese, P.; Petitta, C.; Ascione, B.; Caronna, R.; Guarino, M.; Marignani, M.; Cicala, M.; Chirletti, P.; Malorni, W.; et al.
Abstract Background Lactobacillus species might positively affect gastrointestinal motility. These Gram‐positive bacteria bind Toll‐like receptor 2 (TLR2) that elicits anti‐inflammatory activity and exerts protective effects on damage induced by lipopolysaccharide (LPS). Whether such effect occurs in gastrointestinal smooth muscle has not been established yet. Aim of this study was to characterize the effects of Lactobacillus rhamnosus GG (LGG) and of supernatants harvested from LGG cultures on human colonic smooth muscle and to explore their protective activity against LPS‐induced myogenic morpho‐functional alterations. Methods The effects of LGG (ATCC 53103 strain) and of supernatants have been tested on both human colonic smooth muscle strips and isolated cells in the absence or presence of LPS obtained from a pathogenic strain of Escherichia coli. Their effects on myogenic morpho‐functional properties, on LPS‐induced NFκB activation, and on cytokine production have been evaluated. Toll‐like receptor 2 expression has been analyzed by qPCR and flow cytometry. Key Results Lactobacillus rhamnosus GG exerted negligible transient effects per se whereas it was capable of activating an intrinsic myogenic response counteracting LPS‐induced alterations. In particular, both LGG and supernatants significantly reduced the LPS‐induced morpho‐functional alterations of muscle cells, i.e. cell shortening and inhibition of contractile response. They also hindered LPS‐induced pro‐inflammatory effects by decreasing pro‐inflammatory transcription factor NFκB activation and pro‐inflammatory cytokine IL‐6 secretion, and restored the secretion levels of anti‐inflammatory cytokine IL10. Conclusions & Inferences Taken together these data demonstrate that LGG protects human colonic smooth muscle from LPS‐induced myogenic damage and might be beneficial on intestinal motor disorders due to bacterial infection.